Biosynthesis of lagopodins in mushroom involves a complex network of oxidation reactions. Issue 2 (17th December 2018) - Masuya, Takahiro; Tsunematsu, Yuta; Hirayama, Yuichiro; Sato, Michio; Noguchi, Hiroshi; Nakazawa, Takehito; Watanabe, Kenji
Abstract : Targeted gene knockout in Coprinopsis cinerea, yeast in vivo bioconversion and in vitro assays elucidated the lagopodin biosynthetic pathway, including a complexity-generating network of oxidation steps. Abstract : Use of the ku70 -deficient strain of Coprinopsis cinerea enabled confirmation within the native context of the central role the sesquiterpene synthase Cop6 plays in lagopodin biosynthesis. Furthermore, yeast in vivo bioconversion and in vitro assays of two cytochrome P450 monooxygenases Cox1 and Cox2 allowed elucidation of the network of oxidation steps that build structural complexity onto the α-cuprenene framework during the biosynthesis of lagopodins. Three new compounds were identified as intermediates formed by the redox enzymes.